Hubungan Antara Gaya Belajar dengan Hasil Belajar IPS Siswa Kelas VIII SMP Negeri 2 Demak - Untsa, Fatrikha Najma; Tukidi, Tukidi; Hermanto, Fredy (Universitas Negeri Semarang, 2019)
An educator should be able to realize that every student has different learning styles. By knowing the student's learning style, the teacher can accommodate various learning methods to suit the needs of students. So that all students can get effective ways of learning. This research was conducted in SMP Negeri 2 Demak as a research subject with the aim of finding out the relationship between learning styles with the results of social studies learning of eighth grade students of SMP Negeri 2 Demak. The population in this study were all students of class VIII A-J totaling 338 students and a sample of 138 students using random sampling technique. Collecting learning style data using questionnaires, while social studies learning outcomes are taken from the rapot value of the even semester of 2017/2018 school year. The data obtained is calculated by anova formula with a significance level of 5%, so that the value of F_h 3.29 > F_tab 3.05 means that H_ (a) is accepted. This shows that there is a positive relationship between learning styles and student social studies learning outcomes. Seorang pendidik seharusnya dapat menyadari bahwa setiap anak memiliki perbedaan gaya belajar. Dengan mengetahui gaya belajar siswa, guru dapat mengakomodasikan berbagai metode pembelajaran menyesuaikan dengan kebutuhan siswa. Sehingga semua siswa dapat memperoleh cara yang efektif dalam belajarnya. Penelitian ini dilakukan di SMP Negeri 2 Demak sebagai subjek penelitian dengan tujuan untuk mengetahui hubungan antara gaya belajar dengan hasil belajar IPS siswa kelas VIII SMP Negeri 2 Demak. Populasi dalam penelitian ini yaitu seluruh siswa kelas VIII A-J yang berjumlah 338 siswa dan sampel sebanyak 138 siswa dengan menggunakan teknik random sampling. Pengumpulan data gaya belajar dengan menggunakan angket, sedangkan hasil belajar IPS diambil dari nilai rapot semester genap tahun ajaran 2017/2018. Data yang diperoleh dihitung dengan rumus anova dengan taraf signifikansi 5%, sehingga nilai 3,29 > 3,05 artinya diterima. Hal ini menunjukkan bahwa terdapat hubungan yang positif antara gaya belajar dengan hasil belajar IPS siswa.